“Kung Flu”—The Dynamics of Fear, Popular Culture, and Authenticity in the Anatomy of Populist Communication - Kurilla, Robin (Frontiers in Communication, 2021)
The article presents results of a study on the dynamics between Donald Trump’s use of terms that relate Covid-19 to China and news media publications concerning this use. Qualitative content analysis with elements of discourse analysis was conducted to a) describe the case as a type of populist discourse on Covid-19, and b) illustrate the following hypotheses with the help of empirical material: H1) News media and the dynamics of political communication based on the difference of friend and enemy help legitimizing populist claims and directing public attention toward them while feeding into a narrative of a diffuse category of threats that creates objects of angst and thereby enhances social cohesion. H2) With resources derived from popular culture, populists exploit the culture of political correctness, which is facilitated through the ascription of authenticity. The hypotheses emerged in the course of organizing and preliminarily examining the data collected for an ongoing broader study on populist communication on Covid-19 and its repercussions in different public spheres in view of the following assumptions: A1) Political communication is guided by the distinction of friend and enemy. A2) In populist communication this distinction appears as the difference of ‘the people’ and allegedly corrupt elites, including news media. A3) Angst enhances social cohesion among the audiences of populist speakers directly or mediated by fear. A4) Populist communication is more likely to produce a type of fear that populists benefit from when it depicts the elite as a diffuse category composed of various interlinked enemies. Trump’s contextualized use of the following terms in the time period between March 13 and September 15, 2020, was examined: China flu, China plague, China virus, Chinese plague, Chinese flu, Chinese virus, Wuhan virus, and Kung flu. 38 speeches from Trump’s election campaign or rallies, 28 talks at presidential events or meetings, 47 interviews, 37 press conferences, 35 tweets and 7 re-tweets were subjected to analysis. The case has been successfully described as a type of populist discourse on Covid-19 and both hypotheses have been illustrated with empirical material. In the context of the broader study, the results have an exploratory character.